Long Fatigue Crack Growth in Ti6Al4V Produced by Direct Metal Laser Sintering. (2016) - Konečná, Radomila; Kunz, Ludvík; Bača, Adrián; Nicoletto, Gianni
Abstract: Results of an experimental determination of the propagation of long fatigue cracks in Ti6Al4V alloy prepared by selective laser melting technology are presented. Direct metal laser sintering (DMLS) exploiting EOSINT M270 system was used for fabrication of compact tension specimens having different orientation in relation to the build direction. It has been found that there is no substantial influence of the build orientation and thus the microstructure exhibiting directionality on the growth of long fatigue cracks and on the crack propagation threshold, when optimal process parameters and subsequent stress relieving heat treatments at 380 °C for 8 hours are chosen. The results were compared with literature data on the growth of long cracks in Ti6Al4V alloy manufactured by DMLS technique and with data for conventionally produced forged material. The fatigue crack propagation path, fracture surfaces and fracture surface roughness were investigated. An analysis of the specific microstructure produced by the direct laser sintering was performed and discussed in terms of the mechanism of the propagation of long cracks.